MORFOLOGI CERITA RAKYAT GORONTALO PERANG PANIPI: KAJIAN NARATOLOGI VLADIMIR PROPP - Jafar Lantowa; Mursid Dunggio (Universitas Wijaya Kusuma Surabaya, 2021)
This study examines the morphology of the Gorontalo Folklore of the Panipi War based on Propp's narratological theory. The purpose of this study was to determine the structure of the Panipi War folklore. This study uses a qualitative method with the method of structural analysis of narratology. Data collection techniques using literature study (documentation). The data that has been found were analyzed using structural analysis techniques. Starting with analyzing the findings from heuristic and hermeneutic reading, especially focusing on story morphemes, namely the function of actors who build stories according to Vladimir Propp, consists of 31 actors' functions. Furthermore, it is inserted into the character's action environment which will clarify the character's behavior in the story. The results showed that there were twelve main narrative functions, 3 story patterns with 4 action circles in the Panipi War folklore.